2020
DOI: 10.3389/fvets.2020.587596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooling and Freezing on Llama (Lama glama) Sperm Ultrastructure

Abstract: Semen cryopreservation in South American camelids has a low efficiency. Post-thaw viability of sperm is low, and poor results are obtained when artificial insemination is performed with cryopreserved semen, impeding advances both in accelerated genetic progress and selection. This study aimed to describe the effect of a conventional method of camelid semen cryopreservation on the llama sperm ultrastructure during cooling and freezing, using transmission and scanning electron microscopy (TEM, SEM). Sperm motili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
1
10
1
Order By: Relevance
“…The present approach could also be exploited in semen conservation and thus improve assisted reproduction techniques. In agreement, Sari et al (2020) demonstrated in llama that the addition of 10 or 100 ng/mL of human β-NGF in refrigerated sperm promoted motility and vigour, while viability and mitochondrial activity were maintained. rrb-NGF.…”
Section: Sp B-ngfsupporting
confidence: 64%
“…The present approach could also be exploited in semen conservation and thus improve assisted reproduction techniques. In agreement, Sari et al (2020) demonstrated in llama that the addition of 10 or 100 ng/mL of human β-NGF in refrigerated sperm promoted motility and vigour, while viability and mitochondrial activity were maintained. rrb-NGF.…”
Section: Sp B-ngfsupporting
confidence: 64%
“…Bioinformatic analysis showed that the differentially regulated succinylated proteins in GFE and PFE sperm were distributed in the mitochondria, 25 cytoplasm, 16 nucleus, 8 plasma membrane 6 as well as in the extracellular space 5 (Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…Sperm cryopreservation is an important procedure in the propagation of a variety of species and is often used for the preservation of genetically superior and endangered mammalian species 1 . However, the freeze‐thawing procedure could often result in sperm damage due to the membrane and acrosome injury, 2,3 changes in the mitochondrial membrane potential (MMP), 4 mitochondrial loss as well as axonemal and peri‐axonemal structure disorganization 5 . These can eventually cause up to 50% loss of viable spermatozoa when they are thawed for use 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the coiling of sperm flagella was involved with the alteration of lipid structure in membrane and detachment of plasma membrane from the flagella skeleton (Ozkavukcu et al, 2008; Yeung et al, 2009). Zampini et al (2020) suggested that the ultrastructural alterations could affect the sperm quality in post‐thawed sperm.…”
Section: Discussionmentioning
confidence: 99%